TRUTH WITHOUT RUPTURE: A THEOLOGICAL-RELATIONAL MODEL FOR CONFLICT RESOLUTION IN FAITH COMMUNITIES - Evans Winata; Yonas PAP (CV Naskah Aceh, 2026)
Conflict within Christian faith communities is a pervasive yet frequently mismanaged phenomenon. Existing literature tends to frame church conflict as resolvable primarily through accommodation, separation, or suppression. This article introduces a new conceptual model — Truth Without Rupture — grounded in the lived experience of a practitioner-researcher navigating a sustained theological disagreement within a local faith community in Indonesia. Through an autoethnographic methodology, this study examines how a fundamental distinction between epistemic conflict (disagreement over doctrine and interpretation) and ontological relational identity (shared membership in the body of Christ) enabled conflict to be faced directly, mediated formally, and ultimately transformed into deeper community. Drawing on Romans 14, the theology of Miroslav Volf, and contemporary conflict transformation theory, this article argues that genuine reconciliation in faith communities does not require doctrinal consensus, but rather a theological foundation that renders the other permanently undestroyable as a relational subject. The model further identifies hospitality and servant presence as theological practices that sustain relational integrity throughout conflict. Implications for pastoral counseling, church leadership, and practical theology in pluralistic contexts are discussed.